Analisis Pengambilan Keputusan Taktis Pelaku UMKM (Usaha Mikro, Kecil Dan Menengah) Di Masa Pandemi Covid’19 - Tatik Tatik (STIE Mandala Jember, 2021)
This study aims to analyze the tactical decisions of MSME actors during the Covid-19 pandemic. This research uses a qualitative approach with a case study method. The data used are primary data sourced from in-depth interviews and direct observation. Research respondents were 5 (five) MSME with different business fields. The results showed that the COVID-19 pandemic had several impacts on MSMEs, namely a decrease in turnover and operating profit, difficulty in distributing goods and uncollectible accounts. The tactical decisions taken by MSME players in order to maintain their business are the implementation of WFH (Work From Home) policies, cutting wages, cutting and delaying the payment of THR (Tunjangan Hari Raya), asking for relaxation and restructuring of bank credit, reducing the amount of production and making product innovations or service. Keywords: Tactical Decisions, MSME, Pandemic Covid'19